OPTIMALISASI PENDISTRIBUSIAN IKAN MENGGUNAKAN METODE VOGEL APPROXIMATION PADA NELAYAN MANDALA JAYAPURA - Rangga Ardinsa Putra; Muh. Nur Aksan, Carslen, Ronald Kawena, Ferriwunas, Heru Sutejo (CV. ADIBA AISHA AMIRA, 2025)
The distribution of fish catches by traditional fishermen in coastal areas such as Mandala Village, Jayapura, is a vital activity that supports local economic stability and food security. However, an inefficient distribution system often results in wasted costs and time, as well as reduced fish quality due to delays in delivery. This study aims to design an optimal distribution model by applying a mathematical approach through Vogel's Approximation Method (VAM), which is an initial solution method in transportation problems that considers the highest opportunity cost penalty in each allocation iteration. Data were obtained from field studies, including supply capacity from three main points (Hamadi, Abepura, and Kotaraja), demand from destination stalls, and distribution costs per kilogram. The model was analysed manually and validated using QM for Windows software to ensure the accuracy of the results. The results of the study indicate that the VAM approach is capable of producing a minimum total distribution cost of Rp4,280,000, reflecting significant efficiency compared to the conventional system. Therefore, the application of VAM is recommended as an adaptive distribution strategy that can be integrated into small- to medium-scale fisheries logistics systems in coastal areas